Figure 4 from: Gossner MM, Heckmann R, Moretti M (2018) From the South and from the North? – Quilnus marcosi Heiss & Baena and Aradus angularis J. Sahlberg, two flat bug species new for Central Europe (Hemiptera, Heteroptera, Aradidae). Alpine Entomology 2: 7-14. https://doi.org/10.3897/alpento.2.21801 - Gossner, Martin M.; Heckmann, Ralf; Moretti, Marco (Zenodo, 2018)
Figure 4 Frequency of occurrences of Aradus angularis J. Sahlberg, 1886 with respect to time since fire (left) and elevation (right), based on previous records in Fennoscandia (grey) and the new record in Switzerland (red). Please note that data were available for a subset of records only.